Organic additives used as binders and pore-forming elements of TIO2 ceramics - Santana, Jerusa Goes Aragão; de Campos, Elson [UNESP]; de Melo, Francisco Cristóvão Lourenço (Trans Tech Publications, 2017)
When starches/proteins are added to the ceramic matrix, they originate pores whose morphology and sizes are varied. However, ceramic final properties are influenced by the interaction kinetics amongst particulate materials. This work was designed to analyze the interactions between proteins and disaccharides and their influence on the properties of TiO2 ceramics. Compositions containing protein and protein-sucrose were added to TiO2 powder. Rheological parameters, shear stress and viscosity were studied in order to understand the protein behavior. Furthermore, sintered ceramics were characterized as for porosity, roughness and image analysis by light microscopy. The dispersions produced with sucrose-protein showed lower viscosity and shear stress values and characteristics of a Newtonian fluid. The samples, from compositions which used 40% solids (80 wt% protein and 20 wt%), showed a higher apparent porosity (23.28%) and larger pore sizes (4947.07 µm2).
Keywords: Consolidation; Disaccharide; Titanium dioxide; Vegetable protein